An Investigation of cause and effect relationship between trust and organizational culture based on "Best practice" approach - Jabbar Babashahi; Mahmoud Mohammadi; Reza Qaraeipour; Bograt Rashvand (پژوهش‌های روانشناختی در مدیریت)
One of the main challenges of industrial organizations is retaining Islamic values and developing spirituality that is achieved by increasing trust-building practices such as following justice in payments and managerial behaviors, selecting efficient resources, associate and maintain expert personnel, implementing suitable substitution model, preventing from discrimination between employees and management and application of efficient performance appraisal system. So, the objective of this research is to strengthen culture in light of trust building mechanism such as HR practices in one of industrial organizations. Research methodology includes both descriptive and correlation analysis based on regression. Data was collected by means of designed questionnaire and data samples were selected in probable form. Research results indicated that there is a meaningful relationship between trust and culture. As well as doing constructive HR practices such as performance based compensation system, competence oriented recruitment, result oriented performance management, empowerment, writing job description, using new mechanism of job design and competence based career path management system will result in employees trust.